Diversity and distribution of entomopathogenic fungi in Czech Republic soils - Šimáčková, Kateřina; null, null; Kročáková, Jana; Bohatá, Andrea; Herrero, Noemi (Springer Science+Business Media, 2014)
A survey of entomopathogenic fungi was carried out in cultivated and uncultivated soil habitats in Czech Republic. A total of 189 soil samples were collected during October 2013. Two different methods of isolation were employed, selective media containing cycloheximide and SYLLIT 65 WP and Tenebrio molitor bait method. Entomopathogenic fungi were detected in all collected soil samples by using selective media, but not with the second isolation method. Eight different taxa belonging to five different genera were encountered by using morphological and molecular identification (ITS and EF 1-α molecular markers). The two more common taxa were unnamed species designated as Lecanicillium sp. (14%) and Metarhizium anisopliae (44.5%). Additionally, uncultivated soils showed a higher richness in entomopathogenic fungi than cultivated ones. This is the first time that a monitoring study for the natural occurrence of entomopathogenic fungi was developed covering all Czech Republic. This study constitutes a valuable source for the discovery of indigenous isolates that can be applied in biological control strategies.
Diverzita a distribuce entomopatogenních hub v půdách České republiky
Keywords: Entomopathogenic fungi; monitoring; selective medium; Tenebrio bait method; molecular markers; indigenous isolates; Entomopatogenní houby; monitoring; selektivní půda; metoda odchytu pomocí Tenebrio; molekulární markers; indigenní kmeny